Pengaruh Intellectual Leadership Stimulation dan Pengembangan Sumber Daya Manusia terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Mediasi - Salsabillah, Fatikatun Nisa’; Soelistya, Djoko; Santoso, Rahmat Agus (Gapenas Publisher, 2025)
This study examines the effect of intellectual stimulation leadership, human resource development, and organizational culture on employee performance, with job satisfaction as a mediating variable. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to employees of PT Gresik Mustika Timur and analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS). The results show that intellectual stimulation leadership has a positive effect on employee performance, while human resource development and organizational culture do not have a significant effect. In addition, job satisfaction has a positive effect on employee performance. The mediation analysis indicates that job satisfaction mediates the relationship between intellectual stimulation leadership and employee performance. These findings highlight the importance of intellectual stimulation in leadership practices in enhancing employee performance directly and indirectly through job satisfaction